Complete N and P removal from hydroponic greenhouse wastewater by Tetradesmus obliquus: A strategy for algal bioremediation and cultivation in Nordic countries - Salazar Joao; Santana-Sánchez Anita; Näkkilä Juha; Sirin Sema; Allahverdiyeva Yagut (Elsevier B.V., 2025)
Agricultural wastewaters are a major source of pollution in nature. Here, agricultural wastewaters from a commercial hydroponic greenhouse were used to cultivate the microalga Tetradesmus obliquus sp. NIVA-CHL107 in order to assess its bioremediation ability and evaluate the potential held in biomass derived from wastewater. The batch cultivation trials were performed using a pilot scale indoor photobioreactor equipped with LEDs. The culture achieved 100 % removal efficiency of N and P and a maximum dry weight (DW) of 6.2 g L−1. At the exponential phase of growth, the biomass had a protein content of 45–50 % of DW and a carbohydrate fraction representing 20 % of DW. At the stationary phase, the carbohydrates increased to 60 % of DW. The PUFA content was higher during the exponential phase, representing >65 % of total fatty acids. Throughout the cultivation, the predominant carotenoids were lutein and β-carotene. The Tetradesmus obliquus sp. NIVA-CHL107 was demonstrated to be a suitable candidate for an algal biorefinery designed for hydroponic wastewater treatment and a multi-product pipeline.